Asupan protein, zink, dan defisiensi zink pada santriwati underweight - Vanessa Yudha Azizul Ilmi; Nani Maharani; Fillah Fithra Dieny; Deny Yudi Fitranti (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2021)
Protein intake, zinc intake, and zinc deficiency in underweight female students attending Islamic Boarding School in IndonesiaBackground: One of the nutritional issues in Indonesia is underweight. Groups of teenage girls tend to have underweight especially female students (santriwati) who live far from their parents. It happens due to a lack of macronutrients and micronutrients, zinc deficiency. Zinc deficiency impacts are reproductive disorders, stunted growth, fatigue, and loss of appetite. Objective: Analyzing the differences in zinc levels, protein, and zinc intakes between female students with underweight and normal nutritional status. Methods: An analytical observational study with a cross-sectional design in Askhabul Kahfi Islamic Boarding School with 24 underweight female students selected by consecutive sampling and 24 normal nutritional status female students were selected by matching techniques based on age. Data included nutritional status assessed by BMI for age z-score, protein and zinc intakes assessed by Semi-Quantitative Food Frequency Questionnaire, and zinc levels were tested using Atomic Absorption Spectrophotometry. The data analyses used Mann-Whitney test. Results: Underweight female students had lower average protein intake than normal nutritional status female students (52.20±25.06 and 75.52±23.19 grams) as well as zinc intake (4.63±1.22 and 7.51±1.94 grams). Protein and zinc intake were significantly different, but the two groups did not differ in zinc levels. All subjects had a normal zinc level of 100%. Conclusions: There was a difference in protein and zinc intake between underweight and normal nutritional female students (p<0.001), while the zinc levels were not found any differences (p=0.773).